A people’s religion: the populist impulse in early Kansas Pentecostalism, 1901-1904 - Root, Jonathan B. (Kansas State University, 2009)
This thesis examines early Pentecostalism in light of the Populist Movement. There are two main arguments in this study. First, I maintain that early Kansas Pentecostalism, as seen in the teachings of Charles Fox Parham, was heavily influenced by Populist ideas and language. Parham displayed Populist tendencies in his attacks on the Protestant Establishment, which he believed had neglected to care for the spiritual and physical needs of “the people.” This failure on the part of the churches led Parham to believe that a major reform of the church was needed. Parham went beyond simply criticizing the establishment. He also developed a popular theology that empowered individuals, many of whom were poor and working-class, and created a strong sense of collective aspiration. The second argument of this study is that Populism fostered a sociopolitical environment in which Pentecostalism could thrive. Parham’s confrontations with the Protestant Establishment and his concern with the needs of “the people” was attractive to many individuals who tended to support movements that sought to disrupt the status quo. One event that can shed light on early Kansas Pentecostalism’s relationship with Populism was a revival in Galena, Kansas, a lead and zinc mining town in the southeast corner of the state, that took place from October 1903 to January 1904. By examining some of the connections between the Populist movement and early Kansas Pentecostalism, this study provides some insight into the development of one of the most popular expressions of Christianity in the world.
Keywords: Pentecostalism; Kansas; History, United States (0337)